ANALISIS PELAYANAN TRANSJAKARTA SESUAI DENGAN PERGUB NOMOR 35 TAHUN 2014 (STUDI KASUS KORIDOR 9) - Ovila Marshafeni; Suwanto Adhi; Dzunuwanus Ghulam Manar (Journal of Politic and Government Studies, 2015)
Public services becomes one of a vision of the new Jakarta. Public services in case of public transportation in Jakarta is very important and need more improvements. The improvements that has made in this public services sector began from providing a policy that managing minimum services standart and will be given to the public through Governor regulation no. 34 of 2014 about minimum services standart management unit transjkt-busway. Therefore, it becomes a formulation policy analysis into transjkt services accordance to Governor regulation no 35 of 2014 in services of 9th corridor.The method of this research is descriptive analytical with qualitative approach with the goal of obtaining overview, summary of the situation in the field of various conditions, situations and phenomena that occur in all areas of service in 9th corridor and then will be the analysis of the data obtained in the field.The result showed that transjakarta services in the 9th corridor is basically refferring to Governor Regulation no. 35 of 2014. There are two appraisement about available and unavailable facilities: Some of the facilities in the bus stop and inside the bus already available such as lighting, informations, the ID of vehicles, safety equipment, air conditioner, handlers for standing passengers, sanitary, and facility for difable. However, there are some facilities contained in the policy but not available yet such as lack of security officers in the bus stop, carrying capacity is often forced when the bus full of passengers, light warning signal, arrival and departure information and bus' disruption information. It’s because the limitation of both sides, private and government sectors. Beside that there also, the condition in the field always changing and caused some indicators that target accuracy and regularity of the trip to be blocked. Associated with the efforts made by the government and private sector in improving transportation mode not rated as a significant efforts yet. But both have try to maximize the condition of the bus and the bus stop in case of public service. Research recommendation is in the next research was focused on providing facilities which not available yet to fix the services.